2012
DOI: 10.4236/oju.2012.23023
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Urinary Tract Infections among Males with Lower Urinary Tract Obstruction at Komfo Anokye Teaching Hos-pital, Kumasi, Ghana

Abstract: Purpose: We describe the commonest pathology responsible for lower urinary tract obstruction (LUTO) and associated symptoms such as UTI, etc. among males at the Komfo Anokye Teaching Hospital (KATH) in Kumasi. Materials and Methods: Between January and December 2009, prospective cross sectional hospital based study was conducted involving 103 subjects. Patients with symptoms of LUTO and who were on short admission (up to 48 hours) at the accident and emergency unit of KATH were identified as potential study su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
3
5
1
Order By: Relevance
“…Similarly, all the organisms responsible for UTI in this study were gram negative bacteria, which are the commonest pathogens of the urinary tract [10] [20]. The findings were similar to the one found by Abaeze S, et al in a study on "The prevalence of urinary catheter related infections in Federal Medical Centre, Abeokuta, Nigeria" [21] and Christian Kofi Gyasi-Sarpong, et al at Kumasi, Ghana [22]. In both studies, E. coli was the commonest pathogen isolated, followed by Klebsiella specie.…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, all the organisms responsible for UTI in this study were gram negative bacteria, which are the commonest pathogens of the urinary tract [10] [20]. The findings were similar to the one found by Abaeze S, et al in a study on "The prevalence of urinary catheter related infections in Federal Medical Centre, Abeokuta, Nigeria" [21] and Christian Kofi Gyasi-Sarpong, et al at Kumasi, Ghana [22]. In both studies, E. coli was the commonest pathogen isolated, followed by Klebsiella specie.…”
Section: Discussionsupporting
confidence: 88%
“…The focus of this study was to provide data on antibiotic resistance of uropathogens associated with BOO patients with the goal of improving treatment outcomes of urinary tract infections in the patients. The mean age (69.1 years) of the participants in this study is similar to that of a previous study on urinary tract infection among BOO patients in Kumasi, Ghana in which the mean age reported was 62.0 years [ 8 , 16 ]. The most frequent cause of BOO in this study were benign prostatic hyperplasia (73.9%) and urethral stricture (13.3%), which concurs with the previous study in Kumasi, which reported 76.7% prostatic hyperplasia prevalence and 22.3% urethral stricture [ 8 , 16 ].…”
Section: Discussionsupporting
confidence: 84%
“…The mean age (69.1 years) of the participants in this study is similar to that of a previous study on urinary tract infection among BOO patients in Kumasi, Ghana in which the mean age reported was 62.0 years [ 8 , 16 ]. The most frequent cause of BOO in this study were benign prostatic hyperplasia (73.9%) and urethral stricture (13.3%), which concurs with the previous study in Kumasi, which reported 76.7% prostatic hyperplasia prevalence and 22.3% urethral stricture [ 8 , 16 ]. The prevalence of urinary tract infection among BOO patients in this study (76.6%) is much higher than that reported in Kumasi (40.2%) by Gyasi-Sarpong et al, 2014 [ 8 ].…”
Section: Discussionsupporting
confidence: 84%
“…The current study also showed that Escherichia coli and Coliform spp were the most prevalent uropathogens, accounting for 71.3% of the clinical isolates. Similar studies in Ghana; Kumasi and Cape Coast Hospitals, however, reported Escherichia coli and Klebsiella spp as the most prevalent bacteria isolates responsible for UTI [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 59%